2019
DOI: 10.1111/rda.13417
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic storage of porcine zygotes in serum supplemented with chlorogenic acid

Abstract: Contents The current study was conducted to investigate the effects of 100% foetal bovine serum (FBS) and 100% porcine follicular fluid (pFF) as a storage medium on the developmental competence of porcine zygotes stored at 25°C for 24 hr. Moreover, we evaluated the additive effects of chlorogenic acid (CGA) in the storage medium. When in vitro‐produced zygotes were stored at 25°C for 24 hr in tubes containing either tissue culture medium (TCM) 199 supplemented with 1 mg/ml bovine serum albumin (BSA), 100% of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Moreover, Pomar et al (2004) reported that in vivo‐produced porcine embryos at the morula and blastocyst stages have a feasible developmental quality and viability when stored at 25°C. In a previous study, we also confirmed the development of porcine zygotes up to the blastocyst stage when stored at 25°C for 24 h (Thi Nguyen et al, 2019). In the present study, we observed that the blastocyst formation rate in porcine zygotes stored in 100% FBS supplemented with 50 μM CGA was similar to that of zygotes stored in a chemically defined storage solution.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, Pomar et al (2004) reported that in vivo‐produced porcine embryos at the morula and blastocyst stages have a feasible developmental quality and viability when stored at 25°C. In a previous study, we also confirmed the development of porcine zygotes up to the blastocyst stage when stored at 25°C for 24 h (Thi Nguyen et al, 2019). In the present study, we observed that the blastocyst formation rate in porcine zygotes stored in 100% FBS supplemented with 50 μM CGA was similar to that of zygotes stored in a chemically defined storage solution.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to the medical field, CGA acts as a drug delivery material ( 142 , 143 ), participates in developing new drugs ( 144 , 145 ), etc. In animal husbandry, CGA is added to livestock feed to regulate intestinal flora, and increase the preservation period of animal sperm ( 146 , 147 ), etc. CGA is often involved in cosmetics and daily chemical products due to of its good anti-oxidant and anti-bacterial properties ( 148 , 149 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of antioxidants in the medium used for short‐term storage has been shown to improve embryo survival (Thi Nguyen et al., 2019). In the present study, supplementation of curcumin into a chemically defined solution improved the development of stored embryos.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the potential applications for liquid storage of porcine embryos have been limited. In a previous study, we reported the storage of porcine zygotes using 100% serum enhanced blastocyst formation after short-term storage for 24 hr at 25°C, but the quality of the resulting embryos remained to be improved (Thi Nguyen et al, 2019). In addition, several types of serum-containing or bovine serum albumin (BSA)-containing media have been shown to be effective for short-term storage of porcine embryos (Pomar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation